High Prevalence of Obesity in Acute Promyelocytic Leukemia (APL): Implications for Differentiating Agents in APL and Metabolic Syndrome - Tedesco, Jason (SAGE Publications, 2011)
BACKGROUND: Between January 1999 and December 2008, 469 patients treated for acute myeloid leukemia (AML) were included in this single-institution study. METHODS: We performed a case-control analysis to study the rate of obesity among patients with acute promyelocytic leukemia (APL) and non-APL AML. RESULTS: A total of 81% of APL patients analyzed were obese compared with 41.7% in the non-APL group (p < 0.001). Body mass index (BMI) >30 was seen in 57% of APL patients compared with 31% for the non-APL group (p = 0.01). Neither obesity nor the chemotherapy dosing based on ideal body weight affected survival. CONCLUSIONS: Our findings generate the hypothesis that APL and metabolic syndromes may share a common pathogenic pathway via retinoic acid receptors (RARs), the ligand-controlled transcription factors that function as heterodimers with retinoid X receptors (RXRs) to regulate cell growth and survival. If this link is confirmed in larger studies, our data will instigate further studies using RXR and RAR modulators as a preventive strategy among obese individuals.